LGBTQ politics in Nicaragua : revolution, dictatorship, and social movements - Kampwirth, Karen, 1964- (University of Arizona Press, 2022)
"LGBTQ Politics in Nicaragua provides the previously untold history of the LGBTQ community's emergence as political actors-from revolutionary guerillas to civil rights activists"--